Analysis of Overweight and Obesity, Levels of Physical Activity, and Self-Esteem in School Children of San Pedro Sula, Honduras - Vasquez-Bonilla, Aldo Alfonso; Zelaya-Paz, Constantino; García-Aguilar, Jaime (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2019)
The objective of this study was to analyze the prevalence of overweight, obesity, physical activity levels, and self-esteem of the school children population of San Pedro Sula. The sample was 825 children aged 9-13 years, which were divided into 416 girls and 409 boys. Measurements of BMI (kg/H^2), Physical Activity level (PAQ-C) and Self-esteem (LAWSEQ) were made. A factorial analysis (ANOVA) was performed to observe differences between groups and the Pearson correlation for the study of the relationship of variables with 95% confidence intervals. It was found that 79.8% are in a healthy weight state; 14.8% in overweight and obesity, and 5.3% in malnutrition. It was also found that a moderate level of physical activity predominates in most of the children and a low self-esteem level in 46.9% and average self-esteem of 50.5%. Another finding was that the level of physical activity has a highly positive correlation with sex, being higher in boys than in girls; also physical activity has a very high positive correlation (r = 0.81, p = 0.001) with self-esteem. Our results indicate that children in Honduras show a greater practice of physical activity by children than that of girls. In addition, it was found that a higher level of physical activity could be associated with better self-esteem in children.